The relationship between physical activity levels and serum vitamin D levels varies among children and adolescents in different age groups - Ouyang, Shengrong; Li, Qin; Liu, Zhuo; Yin, Yan (Frontiers in Nutrition, 2024)
Objective The objective of the present study was to explore the relationship between physical activity (PA) levels and serum vitamin D levels in children and adolescents of different ages and sexes. Methods All the data in this study were collected during two cycles (2011–2014) of the National Health and Nutrition Examination Survey (NHANES). Our study participants were aged ≥3 and < 20 years and had valid data for all variables, including vitamin D intake, serum vitamin D levels, PA volume and intensity levels, amount of time spent outdoors, body mass index (BMI), sex, and race. Results A total of 3,312 participants were included in the study; 1,672 were boys (50.4%), and 1,640 were girls (49.6%). A total of 250 (7.5%) children were aged 3–5 years, 1,474 (44.5%) were aged 6–11 years, and 1,588 (47.9%) were aged 12–19 years. Both PA volume and intensity were positively related to serum vitamin D levels in the 6–11-year-old boys and girls (p < 0.05 for both) and in the 12–19-year-old boys. No significant relationship between PA volume or intensity and serum vitamin D levels was detected in the 3–5-year-old group or in the 12–19-year-old girl group. The time spent outdoors and the BMI of the participants had mediating effects on the relationships of PA volume and intensity with serum vitamin D levels in boys and girls aged 6–11 years. Conclusion The relationship between PA and vitamin D varies among children and adolescents of different sexes and ages, and the sun exposure level and BMI had mediating effects on the relationship between PA and the serum vitamin D level. The mechanism of the relationship between PA and increased serum vitamin D levels needs further in-depth research.